The cross-calibration array: a technique to cross-calibrate the energy scales of cosmic-ray experiments using a portable radio array - Mulrey, K.; Buitink, S.; Corstanje, A.; Desmet, M.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; Huesca Santiago, E.; Jhansi, V. B.; Karastathis, N.; Krampah, G. K.; et al. (Proceedings of Science, 2024)
The sources of the highest energy cosmic-rays are still a mystery. One way to try to understand these sources is to measure the energies and composition of cosmic rays and build models that describe their energy spectrum. However, at the highest energies, energy scales between experiments are inconsistent. Directly comparing the energy scales of different experiments is difficult because uncertainties on energy measurements depend on the location, technique, and equipment used. Here, we present a radio-based technique which can be used to cross-calibrate the energy scales of different experiments. The technique relies on a portable array of broadband antennas which measures radiation energy from air showers. This quantity scales quadratically with the electromagnetic energy in the shower, yielding a complete, calorimetric energy reconstruction which can be directly compared at different locations. The array can be deployed at different “host” experiments, measuring radiation energy independently, while the host experiment operates normally. The energy measured by each experiment can then be directly compared using the radiation energy measurements as a standard candle. Using radiation energy to compare the energies measured by different experiments eliminates uncertainties due to different measurement techniques and locations. Using the same detection system at each location eliminates the uncertainties associated with equipment and calibration. In this way, the energy scales of different experiments can be cross-calibrated with minimal uncertainty. Here we present the technique, prospects for event reconstruction, and plans for implementation.
CRIS-Team Scopus Importer:2025-02-04